Some Morphological Observations of Charophytes (Characeae) from Bangladesh - Naz, Sabrina; Diba, Nasrin Jahan (Journal of Life and Earth Science, 2014)
Morphologically interesting charophytes were found from Chapai-Nawabgonj and Rajshahi districts in Bangladesh. These are: swollen branchlet of Lamprothamnium papulosum (Wallr.) J. Groves, long stalked gametangia and twin antheridia of Nitella hyalina (DC.) Agardh, bifid bract cells of Chara flaccida A. Braun and bifid end cell of Nitellopsis obtusa (Desv.) J. Groves. DOI: http://dx.doi.org/10.3329/jles.v7i0.20124 J. Life Earth Sci., Vol. 7: 71-77, 2012